Anti-Angiogenic Effects of Phytochemicals on miRNA Regulating Breast Cancer Progression - Elizabeth Varghese (11008845) (2020)
Several phytochemicals have been identified for their role in modifying miRNA regulating tumor progression. miRNAs modulate the expression of several oncogenes and tumor suppressor genes including the genes that regulate tumor angiogenesis. Hypoxia inducible factor-1 alpha (HIF-1α) signaling is a central axis that activates oncogenic signaling and acts as a metabolic switch in endothelial cell (EC) driven tumor angiogenesis. Tumor angiogenesis driven by metabolic reprogramming of EC is crucial for tumor progression and metastasis in many different cancers, including breast cancers, and has been linked to aberrant miRNA expression profiles. In the current article, we identify different miRNAs that regulate tumor angiogenesis in the context of oncogenic signaling and metabolic reprogramming in ECs and review how selected phytochemicals could modulate miRNA levels to induce an anti-angiogenic action in breast cancer. Studies involving genistein, epigallocatechin gallate (EGCG) and resveratrol demonstrate the regulation of miRNA-21, miRNA-221/222 and miRNA-27, which are prognostic markers in triple negative breast cancers (TNBCs). Modulating the metabolic pathway is a novel strategy for controlling tumor angiogenesis and tumor growth. Cardamonin, curcumin and resveratrol exhibit their anti-angiogenic property by targeting the miRNAs that regulate EC metabolism. Here we suggest that using phytochemicals to target miRNAs, which in turn suppresses tumor angiogenesis, should have the potential to inhibit tumor growth, progression, invasion and metastasis and may be developed into an effective therapeutic strategy for the treatment of many different cancers where tumor angiogenesis plays a significant role in tumor growth and progression. Other Information Published in: Biomolecules License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.3390/biom10020191